関節リウマチ治療中に炎症性腹部大動脈瘤を合併した１例 - 三浦, 貴徳; 本間, 玲子; 飯田, 高久 (臨床リウマチ, 2017)
Inflammatory abdominal aortic aneurysm (IAAA) accounts for 2-14 % of all cases of abdominal aortic aneurysm (AAA). IAAA is a subtype of AAA pathologically characterized by aortic wall thickening, fibrotic change around aneurysm and rigid adherence of the adjacent structures. Recently, IAAA has been a subset of chronic periaortitis, along with idiopathic retroperitoneal fibrosis because of the similarity of histological features between these disease entities. We report here a 50-year-old woman who was diagnosed with IAAA during therapy for rheumatoid arthritis. She was treated with prednisolone 4mg/day, methotrexate (MTX) 8mg/week and golimumab 50mg/month for rheumatoid arthritis. She was also treated with levothyroxine for hypothyroidism induced by radioiodine therapy for Graves’ disease. In 2015, she presented with low grade fever and lower abdominal pain. Computed tomography revealed an abdominal aortic aneurysm and [18F]fluorodeoxyglucose positron emission tomography /computed tomography (FDG-PET/CT) showed the uptake of FDG in thickening wall of aorta. She was diagnosed as having IAAA and the prednisolone was increased to a dose of 30 mg daily, which proved to be effective. 炎症性腹部大動脈瘤は大動脈壁の肥厚，大動脈瘤周囲および後腹膜の線維化，周辺組織との癒着を特徴とした大動脈瘤である．近年，特発性後腹膜線維症と炎症性大動脈瘤は慢性動脈周囲炎という疾患概念に包含されるとする説が示されている．今回，関節リウマチ治療中に発症した炎症性腹部大動脈瘤症例を経験したので，若干の文献的考察を含めて報告する．